Prentice Hall literature : timeless voices, timeless themes GOLD LEVEL. (Massachussets : Pearson, 2003)
It's a powerful combination of the world's best literature and superior reading and skills instruction! Prentice Hall Literature Timeless Voices, Timeless Themes helps students grasp the power and beauty that lies within the written word, while the program's research-based reading approach ensures that no child is left behind.
Spine tinglers : Casey at the bat / E.L. Thayer ; Caucasian mummies mystify Chinese / Keay Davidson -- Challenges and choices : " I have a dream " / Martin Luther King, Jr. ; Old man of the temple / R.K. Narayan -- Moments of discovery : Rules of the game / Amy Tan ; Checkouts / Cynthia Rylant -- Lighter side : Secret life of Walter Mitty / James Thurber ; Jabberwocky / Lewis Carroll -- Visions of the future : Machine that won the war / Isaac Asimov ; Horses / Edwin Muir -- Short stories : Gift of the Magi / O. Henry ; Invalid's story / Mark Twain -- Nonfiction : On summer / Lorraine Hansberry ; Georgia O'Keeffe / Joan Didion -- Drama : Dancers / Horton Foote ; Tragedy of Romeo and Juliet, prologue / William Shakespeare -- Poetry : Dream deferred / Langston Hughes ; Bells / Edgar Allan Poe -- Epic : Siren song / Margaret Atwood ; Ithaca / Constantine Cavafy -- Handbooks : Literary terms handbook ; Writing handbook ; Grammar and mechanics handbook ; Internet research handbook ; Writing criticism and citing sources.
Keywords: LITERATURE